The Analysis of the Students Error in Differentiating Between Nominal and Verbal Sentences in English Songs Lyric - Wulandari, Dewi (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
The aim of this study was to describe the analysis of the students error in differentiating between nominal and verbal sentences in English song lyric by Boy Band Maroon 5. This study was conducted at Politeknik Unggul LP3M Medan. The subject of this study was the students of the second students who have learnt the subject General English II. Descriptive qualitative was the method of this study. This study found that there were 104 errors that the students made in differentiating between nominal and verbal sentences in song lyric of Maroon 5 such as Sugar, She Will be Loved and Payphone. The errors occurred because the students did not know well which was nominal and verbal sentence.